Measurement of telomere length in haematopoietic cells using in situ hybridization techniques. (February 2000) - Martens, U. M.; Brass, V.; Engelhardt, M.; Glaser, S.; Waller, C. F.; Lange, W.; Schmoor, C.; Poon, S. S. S.; Lansdorp, P. M.
Abstract : The DNA of human chromosomes terminates in several kilobases of telomere repeats that are gradually lost with age and with replication in vitro. Defective telomere maintenance has been shown to be causally linked to cell cycle exit and apoptosis. In order to overcome the limitations imposed by Southern blotting, we have established a quantitative fluorescence in situ hybridization (Q-FISH) technique. This technique allows estimation of telomere length in specific chromosome arms from metaphase cell preparations. Furthermore, we have extended quantitative in situ hybridization to flow cytometry (flow FISH) in order to obtain information on the mean telomere repeat content in suspended cells. Telomere length in granulocytes, monocytes, CD8 and CD4 T lymphocytes and natural killer cells was found to differ slightly in the peripheral blood of adults. However, strikingly longer telomeres were observed in B lymphocytes (∼ 1.3 kb longer), suggesting a functional role for telomere maintenance in this cell subset. In summary, Q-FISH and flow FISH represent new methods for measuring telomere length in single cells and allow studies of telomere dynamics in haematopoietic subpopulations at various stages of normal and abnormal antigen responses.